The Role of the Pathologist in the Next-Generation Era of Tumor Molecular Characterization - Valentina Angerilli; Francesca Galuppini; Fabio Pagni; Nicola Fusco; Umberto Malapelle; Matteo Fassan (Diagnostics, 2021)
Current pathology practice is being shaped by the increasing complexity of modern medicine, in particular of precision oncology, and major technological advances. In the “next-generation technologies era”, the pathologist has become the person responsible for the integration and interpretation of morphologic and molecular information and for the delivery of critical answers to diagnostic, prognostic and predictive queries, acquiring a prominent position in the molecular tumor boards.